Role of interlayer coupling in cuprate high-Tc superconductors - Sucheewan Krobthong (2018)
The effect of the interlayer Josephson coupling on the high-Tc superconductors (HTSCs) is re-examined in light of the recent discovery that the critical temperatures, Tc, of the n =4 members of the HTSC homologous series HgBa2Can-1 CunO 2n+2+δ, Tl2Ba2Can-1; Cu n O2n+4+δ and TlBa2Ca n-1CunO2n+3+δ, are lower than those of the n =3 members of the series. This is in contradiction to the prediction of a Ginzburg-Landau theory that the Tc's of a homologous series of HTSCs would increase monotonically with the number of layers. That theory was based on the assumption that the strengths of the Josephson coupling between the different CuO2 layers within a homologous series are the same. It is shown that the Tc's of the n = 4 member in a series would be lower than those of the n =3 member if the hole concentrations in the interior CuO2 layers are different from those in the outer layers.